ANALISIS POTENSI AIR TANAH DANGKAL UNTUK KEBUTUHAN MASYARAKAT DI PADANG ARO KABUPATEN SOLOK SELATAN - Widyawati, Siska; Edial, Helfia; Farida, Farida (Pendidikan Geografi, 2013)
The uncreasing of clean water specially for drinking purpose become a major issue in a lot place in Ind. The good quality and quantity of water are the basic need for the community. This study was conducted to analized the potential for ground water and likely to be developed in order to support the water needs in the city of Padang Aro.This study classified as descriptive research, to illustrate the potential of shallow ground water in the city of Padang Aro in quality (physical, chemical, and biological) as well as the quantity (shallow ground water discharge and water needs for the community) to meet the needs of people living in city of Padang Aro.The results showed that the physical quality of shallow ground water to meet water quality predetermined of Menteri Kesehatan RI. No. 492/MENKES/Per/IV/2010, chemical quality of shallow ground water does not meet the water quality requirements established Ministry of Menteri Kesehatan RI. No. 492/MENKES/Per/IV/2010 and if viewed in terms of the biological quality of shallow ground water does not meet the water quality requirements established of Menteri Kesehatan RI. No. 492/MENKES/Per/IV/2010. Shallow groundwater discharge in Padang Aro relatively very small because the range between 0.061 to 0.013 m3/second m3/second. 60.29% people of Padang Aro using shallow ground water for their daily needs. Where shallow ground water requirement per family ± 404.88 liters / family / day and needs of individuals ± 99.27 liters / person / day. If all residents of Padang Aro using shallow ground water for their lives, then the amount of water needs community as a whole paddock aro ± 1,289,943.9 liters / day. Shallow groundwater discharge contained in Padang Aro daily average is 7551.36 L / day, while the average water requirement per day per family is ± 404.88 liters / family / day, so it can be interpreted that the shallow groundwater in Padang Aro able to meet the water needs of the people in Padang Aro.